2015
DOI: 10.1007/s12263-015-0496-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the hypothalamic transcriptome in response to food deprivation reveals global changes in long noncoding RNA, and cell cycle response genes

Abstract: The hypothalamus integrates energy balance information from the periphery using different neuronal subtypes within each of the hypothalamic areas. However, the effects of prandial state on global mRNA, microRNA and long noncoding (lnc) RNA expression within the whole hypothalamus are largely unknown. In this study, mice were given either a 24-h fast, or ad libitum access to food. RNA samples were analyzed by microarray, and then a subset was confirmed using quantitative real-time PCR (QPCR). A total of 540 mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…There is only one study where the adult expression patterns of hypothalamic lncRNAs under energy availability stress were studied, and that comes from our laboratory 67 . Using Affymetrix exon arrays of WT ad lib fed and fasted mice, we identified over 12,000 lncRNA transcripts in the hypothalamus, 622 of which were differentially-regulated in response to 24-hour fasting.…”
Section: Lncrnas In Endocrine and Metabolic Processes Including Fmentioning
confidence: 99%
See 3 more Smart Citations
“…There is only one study where the adult expression patterns of hypothalamic lncRNAs under energy availability stress were studied, and that comes from our laboratory 67 . Using Affymetrix exon arrays of WT ad lib fed and fasted mice, we identified over 12,000 lncRNA transcripts in the hypothalamus, 622 of which were differentially-regulated in response to 24-hour fasting.…”
Section: Lncrnas In Endocrine and Metabolic Processes Including Fmentioning
confidence: 99%
“…AK038506 was upregulated by approximately 3-fold in fasted compared to ad lib fed mice, while AK049914 showed a nearly 6-fold increase. At the time when writing the original paper 67 , there was no significant homology for AK038506 using a genomic blast, but a new Blast analysis, using a less stringent approach and a ref-seq genomic blast, revealed 99% overlap of 99% of the 1933 nucleotide sequence with two different sequences. The first is the RasAl2 gene on mouse chromosome 1, with homology within an intron between exons 8 and 9.…”
Section: Lncrnas In Endocrine and Metabolic Processes Including Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Dysregulation of lncRNA has been identified to be associated with human diseases, including inflammation and cancer (13)(14)(15). The abnormal expression of lncRNA may contribute to disease initiation and progression through regulating expression of the gene products (16,17). A recent study has reported that differentiation and activation of immune cells are associated with lncRNAs, which have an essential role in autoimmune diseases, including RA (18).…”
Section: Introductionmentioning
confidence: 99%